The Efficacy of Drug-Coated Balloon for Acute Coronary Syndrome - Hirokazu Naganawa; Akira Ito; Shinrou Saiki; Daisuke Nishi; Shinichi Takamatsu; Yoshihisa Ito; Takeshi Suzuki (Cardiology Research and Practice, 2023)
Background. Percutaneous coronary intervention using a drug-eluting stent (DES) is a common therapeutic option for acute coronary syndrome (ACS). However, stent-associated complications, such as bleeding associated with dual antiplatelet therapy, in-stent restenosis, stent thrombosis, and neoatherosclerosis, remain. Drug-coated balloons (DCBs) are expected to reduce stent-associated complications. This study aimed to assess the efficacy of DCB therapy and compare it with that of DES therapy in patients with ACS. Materials and Methods. In this single-center, retrospective, observational study, we examined all patients with ACS treated with DCB or DES between July 2014 and November 2020. Patients with left main trunk lesions were excluded. The primary outcome was a composite of major adverse cardiovascular events (MACE: cardiac death, myocardial infarction, and target lesion revascularization) at one year. Results. Three hundred and seventy-two patients were treated with DES, and 83 patients were treated with DCB. MACE occurred in 10 (12.0%) patients in the DCB group and in 50 (13.4%) patients in the DES group (P=0.73). Conclusions. DCB is a valuable and effective therapy for patients with ACS. Moreover, DCB may become an alternative therapy for DES in patients with ACS.